Sustainable architecture as a strategy for environmental comfort, urban resilience, and climate change mitigation - Cruz, Silvana Heloísa Ferreira; Silva, Valeska Ferreira; Carvalho, Aurilene Sales de (Scientific Journal ANAP, 2025)
Objective - Analyzing how sustainable architecture can contribute to the environmental comfort of users, strengthen urban resilience and mitigate the impacts of climate change.Methodology - This work was done through bibliographic research, with qualitative approach and exploratory character.Originality/Relevance - The growing concern for climate change, the intensification of extreme phenomena and the need to promote more resilient cities highlight the importance of sustainable practices in architecture.Results - Evidence the importance of sustainable architecture as an effective tool in promoting environmental comfort in buildings, providing healthier, efficient and adaptable internal environments to local weather conditions. Theoretical/Methodological Contributions - The bibliographic review allowed a broad and grounded analysis on the concepts of sustainable architecture, environmental comfort, urban resilience and climate change, as well as their interrelationships.Social and Environmental Contributions - Research proposes to contribute socially by encouraging architectural practices that promote environmental comfort, quality of life and the well -being of urban populations. By highlighting sustainable solutions, the study reinforces the importance of built environments that prioritize health, safety and social inclusion, especially in vulnerable communities more exposed to the effects of climate change.
Keywords: Sustainable architecture; Climate change; sustainability